Mango ginger (Curcuma amada Roxb.) may alleviate the effect of high-fat diet/streptozotocin-induced diabetes by activation of the GSK-3?/Fyn/Nrf2 pathway - Yazici, Emrah; Sahin, Emre; Şahin, Nurhan; Tuzcu, Mehmet; Şahin, Kazım; Orhan, Cemal (Wiley, 2023)
Mango ginger (MG) exhibits antioxidant, anti-inflammatory, and antihyperglycemic effects; however, the exact mechanism of action of MG extract in relation to its antidiabetic properties remains unclear. To investigate the potential antidiabetic effect of MG extract, we used a high-fat diet (HFD)/ low-dose streptozotocin (STZ)-induced type 2 diabetic rat model. A total of 28 male Wistar rats were randomly divided into four groups: (i) Control, (ii) MG (50 mg/kg/day of MG extract), ( iii) HFD + STZ (40 mg/kg i.p.), and (iv) HFD + STZ + MG. Following a 12-week administration of MG extract, significant reductions were observed in serum glucose, insulin, free fatty acid, cholesterol, and triglyceride levels in diabetic rats (p <.0001 for all). MG extract supplementation led to an increase in the total antioxidant capacity of the serum and a decrease in malondialdehyde (MDA) levels in both the serum and liver (p <.0001). Furthermore, hepatocellular fat accumulation was partially attenuated in the HFD + STZ + MG group. Notably, MG extract inhibited glycogen synthase kinase-3 beta (GSK-3 beta) in the liver (p <.01) and downregulated Fyn expression, resulting in elevated nuclear factor erythroid 2-related factor 2 (Nrf2) activity in the HFD + STZ + MG group compared to the HFD + STZ group (p <.05). The increased activity of Nrf2 in the HFD + STZ + MG group likely promoted the upregulation of heme oxygenase 1 (HO-1) in the liver (p <.0001). In conclusion, MG extract may exert antidiabetic effects by augmenting the antioxidant defense system through the regulation of GSK-3 beta/Fyn/Nrf2 in a rat model of type 2 diabetes.
Keywords: antioxidant capacity; diabetes; insulin resistance; mango ginger; Nrf2